Pengaruh Pembiayaan Berdasarkan Jenis Penggunaan Terhadap Non Performing Financing Pada Bank Umum Syariah (BUS) Dan Unit Usaha Syariah (UUS) Di Indonesia Periode Januari 2009 – Desember 2015 - Diah Ayu Legowati; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research was to analyze the impact of working capital financing, investment financing and consumption financing on Non Performing Financing of Islamic Banking Industry in Indonesia from January 2009 until December 2015. This research using a quantitative methods. The data used are the secondary data from Financial Services Authority official website. The analytical methods used in this research is the method of multiple linear regression with a significance level of 0,05. Based on the analysis, working capital financing and investment financing partially provide a significant impact on the ratio of non performing financing. Only consumption did not significantly affect the ratio of non performing financing. However, working capital financing, investment financing and consumption financing are simultaneously provide a significant impact on the ratio of non performing financing.